2021
DOI: 10.7494/geol.2020.46.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Change-point detection and trend analysis in monthly, seasonal and annual air temperature and precipitation series in Bartın province in the western Black Sea region of Turkey

Abstract: Studies associated with climate change and variability are of great importance at both the global and local scale in the global climate crisis. In this study, change-point detection and trend analysis were carried out on mean, maximum, minimum air temperatures and total precipitation based on monthly, seasonal and annual scale in Bartın province located in the western Black Sea Region of Turkey. For this aim, 4-different homogenei-ty tests (von Neumann test, Pettitt test, Buishand range test and standard norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In past studies, homogeneity analysis was applied to the total precipitation, maximum, minimum, and average temperature series in different regions of Turkey. When we examine the studies conducted, we can observe that while the homogeneity of the temperature series has deteriorated (Ay, 2020;Yaman & Ertuğrul 2020), it is generally homogenous in the precipitation series , Hırca ve Eryılmaz Türkkan, 2020, Yaman & Ertuğrul 2020, Koycegız & Buyukyıldız 2020. These studies were found to be similar to the results of our results regarding the Van region.…”
Section: Discussionsupporting
confidence: 82%
“…In past studies, homogeneity analysis was applied to the total precipitation, maximum, minimum, and average temperature series in different regions of Turkey. When we examine the studies conducted, we can observe that while the homogeneity of the temperature series has deteriorated (Ay, 2020;Yaman & Ertuğrul 2020), it is generally homogenous in the precipitation series , Hırca ve Eryılmaz Türkkan, 2020, Yaman & Ertuğrul 2020, Koycegız & Buyukyıldız 2020. These studies were found to be similar to the results of our results regarding the Van region.…”
Section: Discussionsupporting
confidence: 82%
“…Despite the lack of water deficiency in the summer months, it can be stated that narrower tree-rings are formed in the years with higher maximal August temperature in this site. Maximum air temperatures in August has shown an increasing trend in Bartın province (Yaman & Ertuğrul 2021). The chain reaction mechanisms of trees to climate and environmental factors are very complicated.…”
Section: Growth-climate Relationships Based Onmentioning
confidence: 99%
“…The melting of the ice caps, in addition to significantly raising the level of the waters of the All-ocean, affects weather changes all over the world. An example of continuous temperature rises in the Bartin province located in the western Black Sea Region of Turkey has already been provided elsewhere (Yaman 2020).…”
Section: Introductionmentioning
confidence: 99%